2011
DOI: 10.4103/0970-9290.93448
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene in the management of oral lichen planus: A placebo-controlled study

Abstract: Lycopene was very effective in the management of OLP, and oxidative stress may have a role in disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 14 publications
2
57
1
Order By: Relevance
“…In our study, complete remission was observed in 66.7% (n=10) and partial remission in 33.4% (n=5) of patients after eight weeks of treatment with prednisolone 40 mg/day along with tapered doses, which was more or less similar to the results reported by Carbone M et al [24] A double blind placebo controlled randomized clinical trial conducted by Saawar N et al [6] transformation (up to 0.2-2%) as compared to another forms. [25,26] Therefore, it may be presumed that lycopene and prednisolone may decrease the risk of malignant transformation in OLP.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In our study, complete remission was observed in 66.7% (n=10) and partial remission in 33.4% (n=5) of patients after eight weeks of treatment with prednisolone 40 mg/day along with tapered doses, which was more or less similar to the results reported by Carbone M et al [24] A double blind placebo controlled randomized clinical trial conducted by Saawar N et al [6] transformation (up to 0.2-2%) as compared to another forms. [25,26] Therefore, it may be presumed that lycopene and prednisolone may decrease the risk of malignant transformation in OLP.…”
Section: Discussionsupporting
confidence: 78%
“…[6,10,11] Daily intake of 3.7 -7 mg may be sufficient to maintain circulating levels of lycopene at levels sufficient to combat oxidative stress, to reduce lipid peroxidation, to decrease inflammation and TNF-α production [19,20,21,22] and the subject with low baseline lycopene levels respond better to low doses of lycopene than the subjects with elevated baseline levels of lycopene. [15] Single oral dose administration is possible because the half-life of lycopene is 2-3 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other treatments included: aloe vera in three trials [21,30,31], hyaluronic acid [26], curcuminoids as adjunctive treatment to prednisone [18], Bacillus Calmette-Guerin polysaccharide nucleic acid [28], topical retinoic acid [6], topical thalidomide [29], lycopene [32], topical isotretinoin [12], ignatia [25] & MuGard [37].…”
Section: Study Characteristicsmentioning
confidence: 99%